Strain‐Driven Dyotropic Rearrangement: A Unified Ring‐Expansion Approach to α‐Methylene‐γ‐butyrolactones. Issue 8 (21st December 2020) - Lei, Xiaoqiang; Li, Yuanhe; Lai, Yang; Hu, Shengkun; Qi, Chen; Wang, Gelin; Tang, Yefeng
Abstract: An unprecedented strain‐driven dyotropic rearrangement of α‐methylene‐β‐lactones has been realized, which enables the efficient access of a wide range of α‐methylene‐γ‐butyrolactones displaying remarkable structural diversity. Several appealing features of the reaction, including excellent efficiency, high stereospecificity, predictable chemoselectivity and broad substrate scope, render it a powerful tool for the synthesis of MBL‐containing molecules of either natural or synthetic origin. Both experimental and computational evidences suggest that the new variant of dyotropic rearrangements proceed in a dualistic pattern: while an asynchronous concerted mechanism most likely accounts for the reactions featuring hydrogen migration, a stepwise process involving a phenonium ion intermediate is favored in the cases of aryl migration. The great synthetic potential of the title reaction is exemplified by its application to the efficient construction of several natural products and relevant scaffolds. Abstract : An unprecedented dyotropic rearrangement of α‐methylene‐β‐lactones has been realized, which provides an enabling tool for the synthesis of various structurally diverse α‐methylene‐γ‐butyrolactones. Distinct from conventional dyotropic rearrangements, the present reactions proceed through either an asynchronous concerted or a stepwise mechanism.